Proving the Crime of Domestic Psychological Violence - male, nismawaty; Arti, Asdar; Nur, Rafika (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to determine the process of proving crimes of psychological violence in domestic violence cases and the factors inhibiting the process of proving crimes of psychological violence in cases of domestic violence. Based on the analysis of data and events, the author concludes that the process of proving psychological violence in cases of domestic violence must use Visum Et Repertum which has the power of proof/valid legal evidence in criminal cases in accordance with the theory of psychological evidence. The type of Visum et Repertum used is Psychiatric Visum et Repertum. From several conclusions examined, it is clear that the judge always bases his conclusions on the Visum Et Repertum submitted in the peace agreement. The inhibiting factors for proving psychological violence in domestic violence cases are made using the legal system theory put forward by Lawrence Friedman and as a result there are still differences in the understanding of law enforcement officials regarding the application of domestic violence laws. (the content of the law) gives rise to differences in perception. Apart from that, it took quite a long time from the incident to the Visum Et Repertum examination, so the autopsy results did not support the trial process (legal structure).